Development and evaluation of ofloxacin orally disintegrating tablets - Badrinath Pralhadrao Mohite; Sandip Annaji Chafle; Jayaprakash Somasundaram; Jasmine Gev Avari (Universidade de São Paulo, 2012)
Bitter taste of ofloxacin, a broad spectrum bactericidal agent, is masked and orally disintegrating tablets were formulated. The bitter taste is masked by forming complex between drug and weak cation exchange resins, Tulsion 335 and Indion 204. Effect of pH and drug:resin ratio on the drug loading was studied. Maximum drug loading was observed at pH 6. Ratio of 1:2 of drug:resin masked almost complete bitterness of ofloxacin. Formation of complexes was confirmed by IR spectroscopy. Physical characterization of taste masked complexes was carried out. Present work envisages the taste masking of ofloxacin and development of orally disintegrating tablets. The effect of pH and resin quantities on drug loading were studied to find the optimum conditions of drug loading for complete taste masking. Effect of superdisintegrants like sodium starch glycolate, croscarmellose sodium and polyplasdone XL at varying level on physical parameters of compressed tablets was also assessed. The formulations containing 5 % w/w polyplasdone XL showed about 90 % of drug release within 5 minutes. No significant differences were observed in the physical parameters of resinates as well as tablets prepared from Tulsion 335 and Indion 204. O gosto amargo de ofloxacina, agente bactericida de largo espectro, é mascarado e formularam-se comprimidos dispersíveis. O sabor amargo é mascarado pela formação de complexo entre o fármaco e resinas de troca catiônica fraca, Tulsion 335 e Indion 204. Efeito do pH e da proporção fármaco: resina sobre a carga de fármaco foi estudada. Carga de fármaco máxima foi observada em pH 6. Proporção 1:2 do fármaco: resina mascarou quase completamente o gosto amargo de ofloxacina. A formação de complexos foi confirmada por espectroscopia no IV. Caracterização física dos complexos de sabor mascarado foi realizada. O presente trabalho preconiza o mascaramento do gosto de ofloxacina e desenvolvimento decomprimidos por via oral, se desintegrando. O efeito do pH e da resina quantidades de carga de fármaco foram estudadas paraencontrar as condições óptimas de carga de fármaco para dissimulação do saborcompleto. Efeito da superdisintegrants como amido glicolato de sódio, croscarmelose sódica e Polyplasdone XL em diferentes níveis de parâmetros físicos de comprimidos também avaliados foi avaliada. As formulações contendo 5 %w/w Polyplasdone XL mostraram cerca de 90% de libertação do fármaco no prazo de 5 minutos. Não foram observadas diferenças significativas nos parâmetros físicos de resinatosbem como comprimidos preparados a partir de Tulsion 335 e Indion 204.